Indonesian EFL Students’ Perceptions on Implementing Differentiated Learning in Learning English - Hesti Maulana; Witri Oktavia (Universitas Negeri Padang, 2023)
The Merdeka Curriculum has just been implemented to resolve Indonesia's long-standing educational issues, specifically the inability of Indonesian students to comprehend simple reading and apply basic math concepts. The two main points highlighted in the Merdeka curriculum are the Pancasila Student Profile Strengthening Project (Projek Penguatan Profile Pelajar Pancasila (P5) and Teaching at the Right Level (TaRL). In order to fulfill the TaRL aspect, differentiated learning is adopted which emphasizes the student-centered learning process and accommodates the different needs of students. This study aims to look at the perceptions of students regarding the implementation of differentiated learning in English language learning. The population of this study were 235 students in tenth grade at SMA Negeri 1 Tilatang Kamang. The samples were 65 students who were randomly selected using cluster random sampling. Descriptive quantitative was used to analyze and describe the questionnaire data. The finding shows (1) learning environment is an important aspect in the successful implementation of differentiated learning strategies in learning English (2) students learn better when given the freedom to learn based on their individual learning profiles (learning styles), learning readiness (abilities), and interests. In conclusion, differentiating content, process, product, and learning environment is an effective and fun learning strategies for students.